2019
DOI: 10.1186/s13613-019-0531-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: peripheral muscular ultrasound in the ICU

Abstract: Muscular weakness developing from critical illness neuropathy, myopathy and muscle atrophy has been characterized as intensive care unit-acquired weakness (ICUAW). This entity occurs commonly during and after critical care stay. Various causal factors for functional incapacity have been proposed. Among these, individual patient characteristics (such as age, comorbidities and nutritional status), acting in association with sustained bed rest and pharmacological interventions (included the metabolic support appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 77 publications
(112 reference statements)
0
69
0
7
Order By: Relevance
“…Electrophysiological assessments are also used to diagnose ICU-acquired weakness and can be applied to unconscious/uncooperative patients. Although CIP and CIM share many features on nerve conduction studies and electromyography, differentiation is possible in ideal circumstances, particularly when the patient is cooperative and voluntary muscle activation is possible (Table 3) [2,5,6,22,30,42]. Single nerve conduction studies have shown promise as alternative for time-consuming full electrophysiological studies [22,31,32].…”
Section: Assessment Of Peripheral Muscle Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiological assessments are also used to diagnose ICU-acquired weakness and can be applied to unconscious/uncooperative patients. Although CIP and CIM share many features on nerve conduction studies and electromyography, differentiation is possible in ideal circumstances, particularly when the patient is cooperative and voluntary muscle activation is possible (Table 3) [2,5,6,22,30,42]. Single nerve conduction studies have shown promise as alternative for time-consuming full electrophysiological studies [22,31,32].…”
Section: Assessment Of Peripheral Muscle Strengthmentioning
confidence: 99%
“…A variety of imaging techniques have been evaluated to assess muscle mass, as a surrogate of muscle strength, some of which also can visualize muscle quality. Of these, ultrasonography is considered most promising [30,33]. Although ultrasonography allows quick and repeated bedside evaluation of measures of muscle quantity and quality, it may underestimate muscle and protein loss [4,30,33,34].…”
Section: Assessment Of Peripheral Muscle Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, US can be combined with EMG and muscle biopsies to provide more targeted acquisition of tissue [61]. Muscle skeletal architecture can be assessed non-invasively even in patients where weakness or pain precludes their cooperation [62]. As the technique is well-tolerated even in children and has no contraindications, it allows for repeated measurements of any muscle accessible on US including facial muscles [63,64].…”
Section: Advantages/disadvantages Of Muscle Ultrasoundmentioning
confidence: 99%
“…This technique has gained favor because it is speedy, easily reproducible and it does not require patient cooperation. Note, however, that the CRIMYNE-2 study excluded diabetic patients [37].…”
Section: Diagnosis Methodsmentioning
confidence: 99%